Reduction of Russia’s Energy Exports: Spatial Distribution of Economic Effects - Natalya Gennadievna Dzhurka; Olga Valeryevna Dyomina (Prostranstvennaâ Èkonomika)
This paper is devoted to the assessment of the size and spatial distribution of economic effects caused by the introduction of sanctions on the export of Russian fuel and energy resources. Leontief’s intra-national balance model with a transparent system of assumptions and relatively low requirements for information support is used in the calculations. The factors of changes in the demand for Russian energy resources in the world markets in the perspective up to 2030 have been analyzed. The paper estimates the reaction of the Russian regional economies in the last year of the forecast period (2030) to a number of successive export restrictions of different nature - from compromise (when the terms of trade remain relatively favorable and the reduction of supplies in the western direction is largely compensated by the activation of supplies in the eastern direction) to extreme/radical (when the practice of trade barriers and sanctions is actively applied, blocking the potential for market maneuvers). It is shown that the spatial distribution of losses from export restrictions is uneven and depends significantly on the geography of new markets for fuel and energy resources. From the point of view of leveling the adverse effects of export restrictions, the following directions of structural transformation of the Russian fuel and energy complex that are currently under active discussion are evaluated: 1) development of the electricity system, 2) creation of new LNG production facilities, 3) modernization of oil refineries and 4) development of oil and gas chemistry. It is concluded that the available proposals allow to compensate for the losses of the national economy arising due to export restrictions, but in general do not change the inertial direction of its dynamics